A Score for Risk of Thrombolysis-Associated Hemorrhage Including Pretreatment with Statins - Erdur, Hebun; Polymeris, Alexandros; Grittner, Ulrike; Scheitz, Jan F.; Tütüncü, Serdar; Seiffge, David J.; Audebert, Heinrich J.; Nolte, Christian H.; Engelter, Stefan T.; Rocco, Andrea (Frontiers in Neurology, 2018)
Background – Symptomatic intracranial hemorrhage (sICH) after intravenous thrombolysis with rt-PA for acute ischemic stroke is associated with a poor functional outcome. We aimed to develop a score assessing risk of sICH including novel putative predictors – namely pretreatment with statins and severe renal impairment. Methods – We analyzed our local cohort (Berlin) of patients receiving rt-PA for acute ischemic stroke between 2006 and 2016. Outcome was sICH according to ECASS-III criteria. A multiple regression model identified variables associated with sICH and receiver operating characteristics were calculated for the best discriminatory model for sICH. The model was validated in an independent thrombolysis cohort (Basel). Results – SICH occurred in 53 (4.0%) of 1336 patients in the derivation cohort. Age, baseline NIHSS, systolic blood pressure on admission, blood glucose on admission, and prior medication with medium- or high-dose statins were associated with sICH and included into the risk of intracranial hemorrhage score. The validation cohort included 983 patients of whom 33 (3.4%) had a sICH. C-statistics for sICH was 0.72 (95%-CI 0.66-0.79) in the derivation cohort and 0.69 (95%-CI 0.60-0.77) in the independent validation cohort. Inclusion of severe renal impairment did not improve the score. Conclusions – We developed a simple score with fair discriminating capability to predict rt-PA-related sICH by adding prior statin use to known prognostic factors of sICH. This score may help clinicians to identify patients with higher risk of sICH requiring intensive monitoring.